Involvement of PKCepsilon in cardioprotection induced by adaptation to chronic continuous hypoxia - Holzerová, K; Hlaváčková, M; Žurmanová, J; Borchert, G; Neckář, J; Kolář, F; Novák, F; Nováková, O (Physiological research, 2015)
Continuous normobaric hypoxia (CNH) renders the heart more tolerant to acute ischemia/reperfusion injury. Protein kinase C (PKC) is an important component of the protective signaling pathway, but the contribution of individual PKC isoforms under different hypoxic conditions is poorly understood. The aim of this study was to analyze the expression of PKCepsilon after the adaptation to CNH and to clarify its role in increased cardiac ischemic tolerance with the use of PKCepsilon inhibitory peptide KP-1633. Adult male Wistar rats were exposed to CNH (10 % O(2), 3 weeks) or kept under normoxic conditions. The protein level of PKCepsilon and its phosphorylated form was analyzed by Western blot in homogenate, cytosolic and particulate fractions; the expression of PKCepsilon mRNA was measured by RT-PCR. The effect of KP-1633 on cell viability and lactate dehydrogenase (LDH) release was analyzed after 25-min metabolic inhibition followed by 30-min re-energization in freshly isolated left ventricular myocytes. Adaptation to CNH increased myocardial PKCepsilon at protein and mRNA levels. The application of KP-1633 blunted the hypoxia-induced salutary effects on cell viability and LDH release, while control peptide KP-1723 had no effect. This study indicates that PKCepsilon is involved in the cardioprotective mechanism induced by CNH.
Keywords: Cell Survival; messenger RNA; inhibitory proteinkinas; Protein Kinase C-epsilon; Adaptation, Physiological; kardiomyocyty; reperfuzní poškození myokardu; krysa rodu Rattus; Hypoxia; zvířata; Myocardial Reperfusion Injury; Myocytes, Cardiac; proteinkinasa C-epsilon; potkani Wistar; hypoxie; Protein Kinase Inhibitors; RNA, Messenger; L-Lactate Dehydrogenase; Rats, Wistar; Male; fyziologická adaptace; Rats; Animals; mužské pohlaví; L-laktátdehydrogenasa; viabilita buněk